Political News Coverage in Philippine Tabloid Sheets: A Critical Discourse Analysis - Bernabe, Michael Steve (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examines the linguistic, discursive, and ideological features of political news in selected Philippine tabloid newspapers using Critical Discourse Analysis (CDA). Anchored on Fairclough’s three-dimensional framework and supported by mediatization and framing theories, the study employed a qualitative content analysis design. A total of 30 political news articles from People’s Journal, People’s Tonight, and Tempo, published between October 2018 and January 2019, served as the corpus. Data were analyzed through systematic coding of morphological, syntactic, grammatical, and discursive features, alongside journalistic roles, news sources, and framing strategies. Findings reveal that tabloid political discourse utilizes modality, passivity, transitivity, and syntactic compression to shape meaning, while discursive elements such as direct and indirect speech, cohesion, and classification contribute to coherence and interpretation. The results also show diverse news topics, multiple journalistic roles, and reliance on authoritative sources, with framing strategies such as game, conflict, human interest, responsibility, morality, economic, and issue framing reflecting underlying political meanings. The study concludes that tabloid news constructs political discourse through strategic language use and selective framing, influencing public perception. It recommends integrating CDA in education and expanding future research using quantitative and comparative approaches. The study aligns with SDG 4 (Quality Education) and SDG 16 (Peace, Justice, and Strong Institutions) by promoting media literacy and critical understanding of political communication. Its sustainability impact lies in strengthening educational, socio-political, and institutional awareness through critical engagement with media discourse.
Keywords: Critical Discourse Analysis; Framing Strategies; Journalistic Roles; Political News Discourse; Tabloid Journalism